Antaryavanikā – the musical part of pūrvaraṅga - Gönc Moačanin, Klara (Array, 2011)
The pūrvaraṅga did not belong to the art of nāṭya. It may consist of fragments of some lost saṃgītaśāstra that were made part of the Nāṭyaśāstra.